Blind Confidence in Automation (Relations industrielles / Industrial Relations, 1956)
SummaryThis is the basic theme of a letter addressed to the president and participants of the 43rd French Social Week in Marseilles. It was sent on behalf of Pope Pius XII by Msgr. Angelo Dell'Acqua, Vatican Substitute Secretary of State for Ordinary Affairs.